Efektifitas Berpikir Kreatif Siswa ditinjau dari Koneksi Matematis dalam Pemecahan Masalah Siswa Kelas VIII SMP Negeri 7 Buton Tengah - Rahmatia Rahmatia; Abdurahman Askois; Ilman Ilman (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
The problem in this research was whether creative thinking was effective reviewed from the mathematics connection in solving problem at SMP Negeri 7 Buton Tengah. The objective of this research was to know the effectiveness of students’ creative thinking reviewed from the mathematics connection in solving problem at SMP Negeri 7 Buton Tengah. This research was experimentalresearch. Population in this research was all grade VIII SMP Negeri 7 Buton Tengah. Sample in this research was taken by using random sampling technique with 44 students consisted of class VIII A as experimental class and VIII B as control class in which each classes consisted of 22 students. Instrument used in this research was test. Research outcome obtained showed that: (1) the result of students’ mean score in pre-test in experimental class was 66.59, while in control class was 62.27. (2) the result of students’ mean score in post-test in experimental class was 80.45, while in control class was 70.68. From hypothesis test result by using t-test, obtained t-count = 3.403 and significant value p = 0.039. Therefore, it could be concluded that students’ creative thinking reviewed from the mathematics connection in solving problem was effective at grade VIII in SMP Negeri 7 Buton Tengah.